2019
DOI: 10.1186/s12967-019-1833-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosome microRNA signatures in patients with complex regional pain syndrome undergoing plasma exchange

Abstract: BackgroundTherapeutic plasma exchange (PE) or plasmapheresis is an extracorporeal procedure employed to treat immunological disorders. Exosomes, nanosized vesicles of endosomal origin, mediate intercellular communication by transferring cargo proteins and nucleic acids and regulate many pathophysiological processes. Exosomal miRNAs are potential biomarkers due to their stability and dysregulation in diseases including complex regional pain syndrome (CRPS), a chronic pain disorder with persistent inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
(43 reference statements)
1
32
0
1
Order By: Relevance
“…Exosomes are membrane-enclosed structures that facilitate communication between cancer cells and the ECM to influence cancer cell survival, growth, and metastasis and the immune system [101]. Cancer-derived exosomes induce the formation of CAFs in the collagen matrix to promote EMT [102] and increase the secretion of MMP-14 to regulate collagen [103].…”
Section: The Relationship Among Exosomes Micrornas and Collagen In Cmentioning
confidence: 99%
“…Exosomes are membrane-enclosed structures that facilitate communication between cancer cells and the ECM to influence cancer cell survival, growth, and metastasis and the immune system [101]. Cancer-derived exosomes induce the formation of CAFs in the collagen matrix to promote EMT [102] and increase the secretion of MMP-14 to regulate collagen [103].…”
Section: The Relationship Among Exosomes Micrornas and Collagen In Cmentioning
confidence: 99%
“…Therefore, identification of specific cargo’s profile associated to pain states might lead to distinguish a specific pathological state from a healthy state and to use exosomes as biomarkers of the diseases. Human studies on CRPS identified specific miRNAs that could be useful to identify subgroup of patients in order to find personalized therapeutic strategies, 14 for example, low level of miR-338-5p in CRPS patients could identify poor responders to plasmapheresis treatment; it could suggest clinicians to evaluate alternative strategies. 45 Moreover, in IBD patients’ exosomes, an overexpression of annexine-1 during inflammatory process than healthy controls has been found, highlighting its potential role as diagnosis biomarker.…”
Section: Exosomes In Different Chronic Pain Conditionsmentioning
confidence: 99%
“…Exosomes’ involvement in pain processes have been demonstrated by studies on different chronic pain diseases, in particular osteoarthritis (OA), 9 , 10 rheumatoid arthritis (RA), 11 inflammatory bowel diseases (IBDs), 12 neurodegenerative pathologies, 13 and complex regional pain syndrome (CRPS). 14 From some of these studies, exosomes appear to be a possible novel therapeutic strategy, 15 transferring cargo in close and distance target cells. They have been even identified as a promising treatment able to improve painful symptoms with fewer side effects, 15 with potential immunoprotective 16 and anti-inflammatory role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The down-regulation of SIRT1 by miRNAs could thus be causally involved in neuropathic pain generation or in the exacerbation of the immune response [51]. Likewise, the increased IL-6 and VEGF expression resulting from decreased activity of miR-338-5p and miR-939, as well as miR-34a and miR-101 targeting Corticotropin releasing hormone receptor 1 (CRHR1) and Karyopherin beta 1 (KPNB1) are relevant candidates for the inflammatory component of neuropathic pain disorders [41,52,53].…”
Section: Introductionmentioning
confidence: 99%